"Stairway to Heaven" or Stairway to the Public Domain: Copyright Infringement of Musical Works Under the 1909 Copyright Act - Ellen Komlos (Washington University Journal of Law & Policy, 2021)
Musical copyright disputes often arise involving various parties, applicable laws, artistic works, and rights at stake. In Skidmore v. Led Zeppelin, the Ninth Circuit considered the scope of copyright protection afforded to works protected under the 1909 Copyright Act, the application of the inverse ratio rule, and the audio version to be played at trial. This Note addresses the clarifications, implications, and remaining sources of confusion resulting from the Skidmore decisions. Part I of this Note examines the history of the Copyright Act and the development of copyright infringement case law in the Second and Ninth Circuits. Part II of this Note describes the harmful effects of the complicated and inconsistent copyright infringement tests. Part III of this Note proposes safeguards to preserve the integrity of the infringement inquiry and further the subsidiary goals of attribution and upfront communication between artists.
Keywords: copyright; copyright protection; copyright dispute; copyright infringement; intellectual property; music; Skidmore v. Led Zeppelin; Copyright Act; 1909 Copyright Act